(untitled) (Singaporean Journal of Business Economics and Management, 2013)
Against a background of serious unemployment and dwindling fortunes of small and medium scale businesses all over Nigeria, the study has a main objective of evaluating the Small and Medium Enterprises Development Agency of Nigeria (SMEDAN) in her support role to cooperative-financed small and medium scale enterprises in Ogun State, Nigeria. The study, designed as a survey, utilized a two-pronged approach in sourcing primary data through the use of questionnaires. Out of the 140 questionnaires administered, 135 were returned representing 96.4% response rate. 27 respondents were officials of Ogun State Cooperative Federation Limited (OGSCOFED), while the remaining 108 were cooperative members who are owners of small businesses in the State. With a Cronbach a coefficient of 0.902, the internal consistency and reliability of the questionnaire was confirmed while the data were analyzed using inferential and descriptive statistics such as simple percentages, rating indices, and the Students t distribution. The study revealed that the services of SMEDAN did not significantly enhance the survival of cooperative-financed small businesses in Ogun State within the study period of 2005-2010. Among the study’s recommendations are that the Federal Government of Nigeria should encourage the small and medium enterprise sector which is the nerve centre of most nations’ industrial sector. Expectedly, this would serve to encourage and engage the army of the nation’s fresh university graduates and subsequently reduce unemployment.